The Role Of Hedonic Motivation Mediating The Effect Of Augmented Reality Marketing On Buying Intention (Study of the Loreal Paris Brand in Indonesia on the Shopee Application) - I Gede Antara Wijaya Kusuma; Putu Yudi Setiawan; Ni Wayan Ekawati; Ni Made Asti Aksari (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study examines the effect of augmented reality-based marketing on consumer purchase intention, with hedonic motivation acting as mediation. In the context of L'Oreal Paris cosmetic products sold on the Shopee platform. This study uses a sample of 110 respondents with 11 indicators to fill out a questionnaire to raise the relevance of augmented reality technology in enhancing a more immersive online shopping experience, namely the merging of the real and digital worlds and the personal world, which can significantly affect consumer purchase intentions. Through the use of the Virtual Try-On AR feature in Shopee, consumers can see the application of cosmetic products virtually on their faces, which not only enhances product information but also provides a fun and satisfying shopping experience. Data was collected from Shopee users in Denpasar, Bali, who have used this augmented reality feature and analyzed using a quantitative approach. The results showed that hedonic motivation plays an important role in mediating the relationship between augmented reality marketing and purchase intention, signifying that emotional satisfaction from the augmented reality experience increases the likelihood of purchase. This research provides valuable insights for digital marketing and e-commerce practitioners to optimize augmented reality strategies in increasing consumer purchase intention. By understanding the effects of augmented reality marketing through hedonic motivation, brands can more effectively design user experiences that are not only informative but also entertaining and emotionally satisfying, thereby increasing consumer purchase intentions.